2010
DOI: 10.1016/j.jhep.2009.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Risk of HCC: Genetic heterogeneity and complex genetics

Abstract: Hepatocellular carcinoma (HCC) is a common form of cancer that arises from hepatocytes and whose risk may be affected by several known environmental factors, including hepatitis viruses, alcohol, cigarette smoking, and others. Rare monogenic syndromes, such as alpha1-antitrypsin deficiency, glycogen storage disease type I, hemochromatosis, acute intermittent and cutanea tarda porphyria, as well as hereditary tyrosinemia type I are associated with a high risk of HCC. Several common conditions or diseases inheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
151
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(154 citation statements)
references
References 71 publications
1
151
0
2
Order By: Relevance
“…HCC cells own common characteristics that are often found to be hepatic stem/progenitor cell biomarkers (2,(6)(7)(8)(9)(10), although multiple environmental and genetic risk factors exist. HCC progression and embryonic liver development share many same properties, and a tumor may originate from progenitor/stem cells that receive abnormal proliferation and maturation signals (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…HCC cells own common characteristics that are often found to be hepatic stem/progenitor cell biomarkers (2,(6)(7)(8)(9)(10), although multiple environmental and genetic risk factors exist. HCC progression and embryonic liver development share many same properties, and a tumor may originate from progenitor/stem cells that receive abnormal proliferation and maturation signals (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…(11,12) We have observed that most HCC occurs obviously in clusters by geographical distribution or by family aggregation in Guangxi, China. Family aggregation of HCC has received researchers' attention for decades.…”
mentioning
confidence: 99%
“…This high background of predisposing environmental factors makes identifying less penetrant genetic contributors more difficult. Familial patterns of susceptibility to liver cancer independent of environmental factors have helped identify a few monogenic metabolic syndromes (e.g., hemochromatosis; Dragani, 2010). However, the analysis of liver tumors points to a variety of other genes that affect liver tumor development.…”
Section: Introductionmentioning
confidence: 99%